2022
DOI: 10.3390/ijerph19127040
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Distributive Injustice and Job Insecurity Amid COVID-19 on Unethical Pro-Organisational Behaviour: Mediating Role of Employee Turnover Intention

Abstract: Drawn on Social Exchange Theory and Conservation of Resources Theory, this study developed a research model to examine the direct influence of job insecurity and distributive injustice, which were common in many hotels amid COVID-19, on unethical pro-organisation behaviour (UPoB) among hotel employees. The study also examines the mediating role of turnover intention in the relationship between job insecurity, and distributive injustice, which was result of the COVID-19 pandemic on UPoB. For this purpose, a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…We identified the relationship between vitality and sustainable performance. Unlike most studies that paid attention to employees’ negative psychological state in the crisis [ 77 ], we noticed the role of vitality at work and explored its relationship with performance from a sustainable perspective. As we have mentioned before, some scholars hold the belief that vitality is an important aspect of employee sustainability [ 78 ]; in the current study, we proved vitality and sustainable performance are separate and vitality could affect it.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the relationship between vitality and sustainable performance. Unlike most studies that paid attention to employees’ negative psychological state in the crisis [ 77 ], we noticed the role of vitality at work and explored its relationship with performance from a sustainable perspective. As we have mentioned before, some scholars hold the belief that vitality is an important aspect of employee sustainability [ 78 ]; in the current study, we proved vitality and sustainable performance are separate and vitality could affect it.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the consideration offered by transformational leaders creates a solid foundation for the management and their employees to reduce employee intention to leave. Additionally, recent studies on hotel workers amid COVID-19 (Alyahya et al 2021;Aliedan et al 2022) showed that workers were negatively affected by inappropriate practices of their management and hence they have an intention to leave the job. Research on transformational leadership in the hotel context pre COVID-19 (Sobaih et al 2022) showed that transformational leadership significantly affects worker intention to stay.…”
Section: Transformational Leadership and Turnover Intentionmentioning
confidence: 99%
“…These strategies included reducing and cutting operational costs, firing part-time and temporary workers, decreasing salaries or laying off a considerable percentage of their workers (Hall et al 2020). Past studies (e.g., Sverke and Hellgren 2002;Dubey et al 2020;Alyahya et al 2021;Aliedan et al 2022) have shown that crises usually have a negative psychological impact on hotel workers and ultimately on their attitudes and behaviors. Nonetheless, surviving employees, who had the opportunity to stay in the organization during the crises became more stressed, anxious, experienced panic and negative emotions, did not feel safe in their place, and were working under extreme pressures both physically and psychologically (Greenberg et al 2020;Howe et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations